Analysis of the level of attention and meditation in children, in the development of online classes caused by the covid-19, through a brain-computer interface - Auccahuasi, Wilver (2020)
ABSTRACT Online classes have become in these times of pandemic by COVID-19, an alternative to continue studying; applied at all educational levels, from schoolchildren to postgraduate studies through University and Technical studies. This study evaluates the levels of attention and meditation applied to children from 8 to 12 years old, when they are doing their virtual classes, using a BCI device, which is installed on the children's head like a headband. Through which the level of attention and meditation is evaluated at the time of taking their classes online. The results show that children when they start their classes have a higher level of concentration compared to when the class is in the middle where children begin to decrease their level of concentration due to distraction, thus increasing their level of meditation. It is concluded that children tend to be distracted when they reach, on average, half the assigned time, this decrease in the concentration level caused by distracting agents, who are at home. Product of the little conditioning that the homes present to carry out academic activities, it is recommended at the time of the virtual classes, it is possible to eliminate, as far as possible these distracting agents, to improve the level of attention and with it a better use of the classes online, it is also recommended that a home environment for these activities be conditioned as much as possible, although being confined at home causes a change in study habits, they must adapt to new ways and one of these is the development of activities that correspond to online classes.